Demonstration and Participatory Evaluation of Different Improved Forage Grass Species in Danan District of Shabele Zone, Somali, Ethiopia (American Journal of Aquaculture and Animal Science, 2025)
The study was conducted at Danan district with the objective of introducing and participatory farm evaluation of improved forage for three improved forage varieties; Sudan grass, Rhodes grass and Panicum maximum were evaluated in randomized complete block design (RCBD) with three replications. Data on growth yield and yield related parameters were collected and analyzed using SAS software. The result indicated that the number of tillers per plant, height biomass yield (qt/ha) were significantly different (P